Mathematical Modeling of Formation of Transparency Regions in Supercooled Stratiform Clouds and Fogs - SHAPOVALOV, Vitaly A.; ADZHIEVA, Aida A.; FEDCHENKO, Lyudmila M.; KOVALEV, Egor A. (Journal of Environmental Management and Tourism; Vol 9 No 1 (2018): JEMT Volume IX Issue 1(25) Spring 2018, 2018)
We developed models of active influence on clouds using crystallization reagents to ensure transparency of the atmosphere. Numerical modeling of various versions of influence on stratiform clouds at aviation seeding was performed. Variation of characteristics of supercooled fogs when bringing man-made crystals was studied. The determination of reagents application rates, estimating impact effect and some other issues were solved using the results of modelling of clouds evolution (both natural and under active influence). Based on generalization of the results of numerical simulation of cloud evolution, the proposals for improvement of cloud seeding technology under different weather conditions are developed.